Effects of Acute Toluene Toxicity on Different Regions of Rabbit Brain. (26th March 2017) - Demır, Mehmet; Cicek, Mustafa; Eser, Nadire; Yoldaş, Atila; Sısman, Turgay
Abstract : The acute phase effects of toluene on the brain have been investigated in this study using rabbit brain via histopathological, immunohistochemical, and biochemical methods. A total of 20 male rabbits were used as control and experimental groups. Moreover, nerve growth factor (NGF), tumor necrosis factor-alpha (TNF-alpha), dopamine (DA), and glial fibrillary acidic protein (GFAP) tests were performed in order to designate the severity of the biochemical damage. In the biochemical evaluation of the prefrontal cortex, hippocampus, hypothalamus, substantia nigra, and entorhinal cortex, the TNF-alpha levels in the brain were found to be significantly higher than in the control group. Levels of dopamine, secreted from the substantia nigra, nerve growth factor (NGF) developed from the hippocampal neurons, and GFAP, secreted from astrocyte cells, were detected to be significantly lower in the toluene-administration group than in the control group (p < 0.05 ). In addition, areas of focal vacuolar degeneration (abscess formation), gliosis, and perivascular demyelination, many pyknotic cells and necrosis were observed. In the toluene-administration group compared to the control group, distinct excessive expansions of the blood vessels and severe degeneration in the structure of cells and also dispersed cell borders were observed. Furthermore, abnormal malformations of the nuclei structure of the oligodendrocyte cells were seen. Bodies of the sequential neurons of the hippocampus in the toluene-administration group were distinctly structurally damaged compared to the control group. In addition, cytoplasm of the cortex cell showed serious immune reactivity in the experimental group.